Reducing architecture to an image - Lewandowska, Agnieszka (Journal of Education Culture and Society, 2019)
Aim. The subject of this work is reduction of architecture complexity to particular image, deprived of its context and time. The author aims to present the problem of perceiving architecture through visual experience only. Methods. The author of the article describes the process of reduction basing on example of iconic sacred building – Church if the Light, designed by Japanese architect Tadao Ando. The analysis of all stages of transformation and reinterpretation of original complex design is conducted. The aim is to indicate how misrepresentation of design and reduction to particular image was transferred to architecture once again. Results and Conclusion. The essential conclusion of the article is the impact and power of image culture. The author of the article indicates how contemporary world of pictures influences human perception of space and limit it to one sense – sight.